"Everything of value from over a thousand years of achievement" - Olszówka, Marcin (A thousand years of Poland's presence among the elite of European states, 2026)
The preamble to the 1997 Constitution of the Republic of Poland — which is normative rather than ornamental in character — establishes numerous obligations, many of them interrelated. One of these is the duty, resting primarily on public authorities but also on society as a whole, to pass on to future generations everything of value from over a thousand years of Polish statehood. "That which is of value" undoubtedly includes attachment to European civilization, of which the most prominent expressions are the verbalized presence of the Catholic Church in Polish constitutionalism and Polish culture — rooted in the Christian heritage of the Nation and serving as a vehicle for universal values: truth, justice, goodness, and beauty. The fulfillment of this obligation is contingent upon the preservation of sovereignty, including the supremacy of the Polish constitution within the legal order.